PARTICLES IN VASYL STEFANYK’S IDIO-STYLE: SEMANTIC-PRAGMATIC ASPECT - Dzhochka, Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article examines particles of the Ukrainian language in Vasyl Stefanyk’s novellas. Particles, considering a wide range of communicative functions, intonational setting, positional mobility etc., are one of defining classes of discursive words, which, along withother lingual means, form and define the structure of any fictional canvas. During the research both general scientific methods (analysis, synthesis, generalization), as well as linguistic ones (contextual, transformational) were utilised. The aim of the proposed study is establishing semantic-pragmatic senses of frequent particles in the analysed text that serve as devices of actualizing various spiritual, mental, social characteristics of novellas’ heroes. In the specified perspective the results of the scientific research are: the discovery of the most frequent particles, characteristic of the writer’s idio-style, namely: a, ta, to, zhe (zh), koby, nai, the definition of usual senses of particles, directed at communication (internal dialogism and communicative memory (the particle a), natural communication, combined with the increase of certain components of an utterance (the particle ta)), the guidelines on conscious definiteness and detachment from the depicted and so on. The practical significance of the researchlies in the analysis of particles in Vasyl Stefanyk’s fictional text as discursive words acting as means of the text cohesion and coherence, performing anaphoric and cataphoric functions etc., acting, meanwhile, as one of important lingual components of the author’s individual style. The novelty of scientific theses lies in the fact that for the first time the fictional text of V. Stefanyk’s novellas is examined through the prism of a communicative approach with the aim to establish semantic-pragmatic senses of particles as important elements of the discourse structure.